Screening of Active Principles from a Few Medicinal Plants - Rajput, A.P. (Asian Journal of Chemistry, 2010)
Medicinal plants are gaining importance because of their commercial and therapeutic values. The demand for medicinal plants is very high as they are considered as a warehouse of many secondary metabolites. Among secondary metabolites various groups play key roles; these need much concentration and detailed study. In the present study 20 medicinal plants used extensively by tribals of Satpuda have been screened qualitatively to find out their active principles.